2008
DOI: 10.1530/eje-08-0293
|View full text |Cite
|
Sign up to set email alerts
|

Retesting the childhood-onset GH-deficient patient

Abstract: GH deficiency (GHD) in adults has to be shown by a single provocative test, provided that it is validated. Insulin tolerance test (ITT) has been indicated as the test of choice; now also glucagon test is validated and represents an alternative. The GHRH plus arginine (ARG) test and testing with GHRH plus a GH secretagogue are equally reliable diagnostic tools, and are now considered as 'golden' standards as ITT. Childhood-onset (CO) GHD needs retesting in late adolescence or young adulthood; this is a major cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 45 publications
2
11
0
4
Order By: Relevance
“…Similar was the statement of Quigley et al [8] who performed a single GH stimulation test to reassess the patients with multiple pituitary hormone deficiency, and two tests to confirm persistent isolated GHD. Moreover, our findings point at the possibility of using the test with clonidine in transition period, although that test has not been recommended in adults [6,9,17]. It seems worth mentioning that -in our study -almost half of the patients with decreased GH peak in ITT had a normal GH peak in the test with clonidine.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Similar was the statement of Quigley et al [8] who performed a single GH stimulation test to reassess the patients with multiple pituitary hormone deficiency, and two tests to confirm persistent isolated GHD. Moreover, our findings point at the possibility of using the test with clonidine in transition period, although that test has not been recommended in adults [6,9,17]. It seems worth mentioning that -in our study -almost half of the patients with decreased GH peak in ITT had a normal GH peak in the test with clonidine.…”
Section: Discussionmentioning
confidence: 54%
“…According to the current recommendations [1,3,6,17], in order to confirm GHD after the completion of growth-promoting therapy, it is sufficient to prove decreased GH peak in only one stimulation test. However, it has also been recently suggested that two stimulation tests should be used in order to diagnose isolated GHD in adults (due to a significant falsepositive error rate in GH response in a single test) [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niinikoski et al (2011) observed in four LPI children very low IGF-1 concentrations (5-13 nmol/L), despite arginineinsulin GH provocative test revealed an abnormal GH peak level (< 10 ug/L) in only one of the patients. Nevertheless, a normal GH response to provocative tests in patients with auxology suggestive of GHD does not definitively rule out GHD because they may have a low spontaneous GH secretion over 24 h, likely reflecting GH neurosecretory dysfunction (Gasco et al 2008). Moreover, today, there is no gold standard for estimating GH secretion in LPI Reference range is also indicated Reference range is also indicated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples for the GH analysis are obtained at 0, 15, 30, 45, 60, 90 and 120 minutes. The cut-of for this test is 20 ng/ml for the GH peak in childhood and 19.0 ng/ml in late adolescent and early adulthood [43]. Furthermore, the GHRH plus arginine test is useful for identifying false positive GHD in children showing a blunted GH response to classic stimuli in contrast with a normal growth rate [44].…”
Section: Provocative Gh Testingmentioning
confidence: 99%